“You Don’t Have A History”: Passion as the Counter-Narrative of Heritage, History, and Archives: Closing Keynote Speech - Williams, Dorothy (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2023)
This paper describes my lifelong journey as a historian, heritage activist and librarian-archivist focused on recovering and sharing the history of Quebec and Canada’s English-speaking Black communities. This paper yet again contends that this community faces silence and invisibility. I share personal and professional examples of how I became passionate about Black history and I reveal the real-life consequences of its erasure. From this context, I provide detail on how this passion fueled decades of research, storytelling, and the building of collections and historical and archival materials. Over three decades ago, I responded with groundbreaking books: Blacks in Montreal 1628-1986: An Urban Demography (1989), and The Road to Now: A History of Blacks in Montreal (1997). Since that time, I have written extensively on the need to reshape Canada’s narrative so that it may embrace the diversity we boast about. I share how my efforts to address our cultural ignorance have led to the recent creation of the ABC’s of Canadian Black History Kit. Finally, my article concludes with an underscoring of how that very passion was rooted in my life’s mission to counter my own invisibility in Canada’s narrative.